The use of health literacy by an academic league in the information process in times of pandemic: Experience report (Research, Society and Development, 2021)
The objective of this study is to report the experience of the Academic League of Urgency and Emergency (LAUE) of the University of the State of Minas Gerais (UEMG) in relation to events organized by students and professors of the participating Nursing course using videoconference platforms for the realization lectures and short courses due to the social isolation caused by the COVID-19 Pandemic involving the informational process of health literacy. This is a quantitative, descriptive study, of the type of experience report of students of the nursing course about the use of technology in the development of educational activities. 79 participants of this study participated in events held by the Academic League and 15 LAUE students from courses in the health area. The activities took place between the months of October and December 2020, using remote means. The use of technologies during the period of social isolation proved to be satisfactory, reinforcing that their use plays a facilitating role in the teaching and learning process during the period of social isolation. Through the internet it was possible to obtain a greater reach of people, allowing to foster health literacy with the use of digital media, promoting knowledge based on scientific evidence and being able to observe a greater interaction of listeners with the speakers during the events held. In view of this, the use of videoconferencing platforms played a facilitating role in the process of building knowledge, having as an ally the technologies that provide increasingly effective and modern communication between people who may be in different spaces.